Designing a proposed e-training program to the development of technical skills among female teachers of public education in Bisha governorate - Al-Shahrani, Sarah Ali; Bassiouni, Abeer Badir (Journal of Educational and Psychological Sciences, 2022)
This study aimed at designing an e-training program for the developing some technical skills among secondary school female teachers in Bisha governorate, to achieve that, the study used the quasi-experimental approach based on one group and the pre- and post-application of the study tool. The study population consisted of public education female teachers affiliated of the Department of Education in Bisha Governorate in the secondary stage, in the academic year 1442-1443 AH, of (1385) female teachers, and the study sample consisted of (104) female teachers. The researcher designed the e-training program, built the observation card and pre and post-applied it to the study sample. The results showed that there was a statistically significant difference between the average scores of the study sample in the pre and post application of the observation card of cloud storage skills on Google Drive and between the average scores of the pre and post application of the observation card of the skills of teacher kit app in favor of the post application. The training program also proved its effectiveness in achieving its desired objectives. The study recommended that digital skills of female teachers related to cloud storage and Teacher kit app skills should be enhanced and that female teachers should be encouraged to use them in teaching.
Keywords: Cloud storage; Gmail; Google drive; Teacher kit app